2014
DOI: 10.1016/j.ophtha.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between In Vitro Susceptibility to Natamycin and Voriconazole and Clinical Outcomes in Fungal Keratitis

Abstract: Purpose To assess the association between minimum inhibitory concentration (MIC) and clinical outcomes in a fungal keratitis clinical trial. Design Experimental study using data from a randomized comparative trial. Participants Of the 323 patients enrolled in the trial, we were able to obtain MIC values from 221 patients with monocular fungal keratitis. Methods The Mycotic Ulcer Treatment Trial I (MUTT I) was a randomized, double-masked clinical trial comparing clinical outcomes of monotherapy with topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…In addition, because the selected nonantifungal agents have already demonstrated safety when applied to the ocular surface, combined formulations could be developed and deployed quickly. A potential limitation of the present study is that it involves exclusively in vitro experiments, and it has been shown with Fusarium species that in vitro susceptibility does not necessarily correlate with the in vivo clinical response (33). Therefore, future work should evaluate the translation of these preliminary in vitro findings to in vivo animal or human trials.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, because the selected nonantifungal agents have already demonstrated safety when applied to the ocular surface, combined formulations could be developed and deployed quickly. A potential limitation of the present study is that it involves exclusively in vitro experiments, and it has been shown with Fusarium species that in vitro susceptibility does not necessarily correlate with the in vivo clinical response (33). Therefore, future work should evaluate the translation of these preliminary in vitro findings to in vivo animal or human trials.…”
Section: Resultsmentioning
confidence: 98%
“…3 Reduced success in the treatment of corneal ulcers has also been associated with increasing MICs to voriconazole. 1 Treatment with azoles before presentation and enrollment in MUTT I was not shown to increase voriconazole MICs. 11 This finding suggests that the increased resistance patterns observed in this study are not owing to treatment of disease with antifungals.…”
Section: Discussionmentioning
confidence: 96%
“…1 The mechanism for azole resistance in filamentous fungi may be a mutation in the CYP51 gene responsible for producing the lanosterol-14α-demethylase enzyme, which is the drug target. 2 Development of resistance has been documented in patients with chronic fungal infections such as pulmonary aspergillosis after prolonged use of triazole antifungals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, testing of drug susceptibility of fungal species seems important for the final treatment outcome. However, the guidelines for antifungal susceptibility testing in treatment of fungal keratitis have not been well established,9 and the clinical trials are very few in numbers.…”
Section: Introductionmentioning
confidence: 99%